INJURIES AND ACCIDENTS IN CONSTRUCTION AND MEASURES FOR THEIR PREVENTION - BAYZAKOV A.A, (European Journal of Life Safety and Stability (2660-9630), 2021)
The relevance of this topic is due to the growth of injuries in the construction industry. The purpose of the article is to study the causes of emergencies in the construction industry and determine measures to reduce injuries.